Development of Teaching Materials that Contain Life Skills Values on Utama Junior High School Teacher, Depok - Reni Rokhayati; Memmy Dwi Jayanti (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Teacher in the learning process is not only required to make up the pattern of student centered learning. Teaching materials are interesting, creative, and innovative needs to be done, so that learning is not monotonous and students can apply a skill that is used when it works or not.Skills in question are life skills for someone tu run his life wherever located.This research carried out in Utama secondary schools with the number of 20 people, precisely at the semester begins March to June 2015. The goal of making teaching materials to facilitate teachers in delivering the curriculum in the classroom where the material does not expect 2013 to be receiving only. Value life skill that is found in teaching materials teacher Utama Junior High School consists of skills: Thinking Skills(8,3%), manage skills (16,7%), related skills ( 25%), care skills (8,3%) gives skills (16,7%), working skills ( 25%).